Racial disparities in septic shock mortality: a retrospective cohort studyResearch in context - Lauren P. Black; Charlotte Hopson; Michael A. Puskarich; Francois Modave; Staja Q. Booker; Elizabeth DeVos; Rosemarie Fernandez; Cynthia Garvan; Faheem W. Guirgis (The Lancet Regional Health. Americas, 2024)
Summary: Background: Patients with septic shock have the highest risk of death from sepsis, however, racial disparities in mortality outcomes in this cohort have not been rigorously investigated. Our objective was to describe the association between race/ethnicity and mortality in patients with septic shock. Methods: Our study is a retrospective cohort study of adult patients in the OneFlorida Data Trust (Florida, United States of America) admitted with septic shock between January 2012 and July 2018. We identified patients as having septic shock if they received vasopressors during their hospital encounter and had either an explicit International Classification of Disease (ICD) code for sepsis, or had an infection ICD code and received intravenous antibiotics. Our primary outcome was 90-day mortality. Our secondary outcome was in-hospital mortality. Multiple logistic regression with Least Absolute Shrinkage and Selection Operator (LASSO) for variable selection was used to assess associations. Findings: There were 13,932 patients with septic shock in our cohort. The mean age was 61 years (SD 16), 68% of the cohort identified as White (n = 9419), 28% identified as Black (n = 3936), 2% (n = 294) identified as Hispanic ethnicity, and 2% as other races not specified in the previous groups (n = 283). In our logistic regression model for 90-day mortality, patients identified as Black had 1.57 times the odds of mortality (95% CI 1.07–2.29, p = 0.02) compared to White patients. Other significant predictors included mechanical ventilation (OR 3.66, 95% CI 3.35–4.00, p < 0.01), liver disease (OR 1.75, 95% CI 1.59–1.93, p < 0.01), laboratory components of the Sequential Organ Failure Assessment score (OR 1.18, 95% CI 1.16–1.21, p < 0.01), lactate (OR 1.10, 95% CI 1.08–1.12, p < 0.01), congestive heart failure (OR 1.19, 95% CI 1.10–1.30, p < 0.01), human immunodeficiency virus (OR 1.35, 95% CI 1.04–1.75, p = 0.03), age (OR 1.04, 95% CI 1.04–1.04, p < 0.01), and the interaction between age and race (OR 0.99, 95% CI 0.99–1.00, p < 0.01). Among younger patients (<45 years), patients identified as Black accounted for a higher proportion of the deaths. Results were similar in the in-hospital mortality model. Interpretation: In this retrospective study of septic shock patients, we found that patients identified as Black had higher odds of mortality compared to patients identified as non-Hispanic White. Our findings suggest that the greatest disparities in mortality are among younger Black patients with septic shock. Funding: National Institutes of Health National Center for Advancing Translational Sciences (1KL2TR001429); National Institute of Health National Institute of General Medical Sciences (1K23GM144802).